Erosion wear behaviour of 3 mol-% yttria-stabilised zirconia ceramics by solid particle impact at elevated temperatures. (April 2015) - Fang, M. H.; Liu, F. J.; Huang, Z. H.; Min, X.; Liu, Y. G.; Ji, H. P.; Tang, H.; Wu, X. W.; Peng, F.
Abstract : The solid particle impact erosion wear behaviour of 3 mol-% yttria-stabilised zirconia ceramics is studied at elevated temperatures. The influence of erosive temperature on the erosion wear resistance and erosion mechanism of 3 mol-% yttria-stabilised zirconia ceramic at the impact angle of 90° is investigated. The results show that material removal rate of volume erosion wear of 3 mol-% yttria-stabilised zirconia ceramics increases with rising temperature. The erosion rate increases slowly between room temperature and 600°C. The 3 mol-% increases rapidly between 800 and 1200°C. The maximum erosion rate of 0·55 mm 3 g −1 is found at 1200°C. The increase of the erosion wear rate is because of the decrease of the mechanical properties at high temperatures. The erosion wear mechanism of 3 mol-% yttria-stabilised zirconia ceramics is temperature-dependent, which is mainly plastic deformation below 800°C and mainly cracking in irregular crisscross patterns leading to the flaky exfoliation of material, between 800 and 1400°C. The results provide an insight into the mechanism of material damage and failure of advanced ceramics by high temperature erosion.